Benefits and problems of health‐care robots in aged care settings: A comparison trial. (13th September 2015) - Broadbent, Elizabeth; Kerse, Ngaire; Peri, Kathryn; Robinson, Hayley; Jayawardena, Chandimal; Kuo, Tony; Datta, Chandan; Stafford, Rebecca; Butler, Haley; Jawalkar, Pratyusha; Amor, Maddy; Robins, Ben; et al.
Abstract : Aim: This study investigated whether multiple health‐care robots could have any benefits or cause any problems in an aged care facility. Method: Fifty‐three residents and 53 staff participated in a non‐randomised controlled trial over 12 weeks. Six robots provided entertainment, communication and health‐monitoring functions in staff rooms and activity lounges. These settings were compared to control settings without robots. Results: There were no significant differences between groups in resident or staff outcomes, except a significant increase in job satisfaction in the control group only. The intervention group perceived the robots had more agency and experience than the control group did. Perceived agency of the robots decreased over time in both groups. Overall, we received very mixed responses with positive, neutral and negative comments. Conclusions: The robots had no major benefits or problems. Future research could give robots stronger operational roles, use more specific outcome measures, and perform cost–benefit analyses.